MATHEMATICAL MODELING OF THERMAL PROCESSES IN TRUNCATED CONICAL SOLAR WATER HEATERS - Esanaliyeva, N.R. (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2026)
This article examines the mathematical modeling of thermal processes occurring in a truncated conical solar water heater collector. These collectors are crucial in enhancing energy efficiency and developing environmentally friendly heat sources. During the modeling process, convection, heat conduction, and radiative heat transfer processes are clearly expressed based on the Navier-Stokes equations. The complex nature of heat flow, the geometric characteristics of the collector, and the non-uniform absorption of solar radiation are all taken into account in the model. A three-dimensional system of differential equations, which describes the conservation of mass, momentum, and energy transfer, is used as the basis of the mathematical model. Also, the correct definition of boundary and initial conditions ensures that thermal processes are modeled in accordance with real conditions. The results of this study have served to increase the efficiency of solar water heater collectors and provide a deep analysis of heat exchange processes.